Dynamic Microtubule Arrays in Leukocytes and Their Role in Cell Migration and Immune Synapse Formation - Kopf, Aglaja; Kiermaier, Eva (Frontiers in Cell and Developmental Biology, 2021)
The organization of microtubule arrays in immune cells is critically important for a properly operating immune system. Leukocytes are white blood cells of hematopoietic origin, which exert effector functions of innate and adaptive immune responses. During these processes the microtubule cytoskeleton plays a crucial role for establishing cell polarization and directed migration, targeted secretion of vesicles for T cell activation and cellular cytotoxicity as well as the maintenance of cell integrity. Considering this large spectrum of distinct effector functions, leukocytes require flexible microtubule arrays, which timely and spatially reorganize allowing the cells to accommodate their specific tasks. In contrast to other specialized cell types, which typically nucleate microtubule filaments from non-centrosomal microtubule organizing centers (MTOCs), leukocytes mainly utilize centrosomes for sites of microtubule nucleation. Yet, MTOC localization as well as microtubule organization and dynamics are highly plastic in leukocytes thus allowing the cells to adapt to different environmental constraints. Here we summarize our current knowledge on microtubule organization and dynamics during immune processes and how these microtubule arrays affect immune cell effector functions. We particularly highlight emerging concepts of microtubule involvement during maintenance of cell shape and physical coherence.